THE EFFECTIVENESS OF IMPLEMENTING RISK MANAGEMENT FRAMEWORKS IN HEALTHCARE ORGANIZATIONS - Sami Sayyaf Alruwaili, Sultan Nahis Duaibl Alanazi, Saif Saad Abdullah Alshahrani, Majed Ahmed Al-Homrany, Ali Abdullah Al-Kathiry, Huthayfah Yahya Jabril Hakami, Abdullah Othman Ali Bahri, Riyadh Abdullah Abdu Barakat, Maram Mohammed Alkhaibari,,; Amjad Mohammed Khuraybah, Amjad Abdullah Aljuwaysir, Majed Awadh Alazmi, Ibrahim Awad Alazmi, Abdulkarim Marzooq Alhujaily, Ibrahem Marzoq Alboqami, Abdulrahman Muayjil Almutairi, Tahani Shulaywih Owayyish Alzabeni, (Chelonian Research Foundation, 2022)
This study aimed to provide a framework and effective strategies for integrating risk management (RM) in executive levels of healthcare organizations (HCOs) and identifying potential areas for future research in this sector. A comprehensive evaluation was done to examine all papers written in English language and available in the major bibliographic databases. Two impartial reviewers conducted the review selection and characterisation using pretested forms. A thorough and straightforward risk management framework is established for the executive levels of HCOs, based on the results and in accordance with the ISO31000 standard. The process consists of five primary stages: context establishment, risk assessment, risk treatment, monitoring and review, and communication and consultation. Furthermore, a collection of tools and strategies were proposed for implementation throughout each stage. The suggested methodology was used to assess the state of risk management in the executive levels of HCOs. The framework serves as a training tool for successful risk assessment and also as a tool for evaluating non-clinical hazards in healthcare organizations. Healthcare organization managers should use a variety of risk management techniques and tools to assure high quality. They should choose these methods and tools based on their specific needs and should not assume that any one tool is all-encompassing. Keywords: organization, risk management, review, risk analysis, health care, executive levels.